Morphological and quantitative CT features of anterior mediastinal lesions in TAFRO syndrome and idiopathic multicentric Castleman disease - Mohamed, Lamiaa; Umeda, Masataka; Tsutsui, Shin; Toya, Ryo; Umetsu, Ayaka; Otsuka, Mizuna; Endo, Yushiro; Shimizu, Toshimasa; Fukui, Shoichi; Sumiyoshi, Remi; Kawakami, Atsushi; Koga, Tomohiro (Frontiers in Immunology, 2025)
We investigated the diagnostic challenges of TAFRO syndrome and idiopathic multicentric Castleman disease (iMCD), focusing on the usefulness of anterior mediastinal lesions for distinguishing the disease subtypes. A comparative analysis using computed tomography (CT) imaging was performed for three patient groups: TAFRO without iMCD/iMCD-TAFRO (n=13), iMCD-idiopathic plasmacytic lymphadenopathy (IPL)- not otherwise specified (NOS) (n=16), and IgG4-related disease (IgG4-RD) (n=59). Lesions were categorized into increased fat density, micronodular opacity, and mass. The lesions’ CT attenuation values were compared, and receiver operating characteristic (ROC) curve analyses assessed their diagnostic relevance. Anterior mediastinal lesions were most frequent in the TAFRO without iMCD/iMCD-TAFRO group (85%) compared to the iMCD-IPL/NOS group (31%) and IgG4-RD group (6.8%). Distinct patterns such as increased fat density were predominantly observed in the TAFRO without iMCD/iMCD-TAFRO group. The CT values showed significant intergroup differences, with ROC analyses confirming high diagnostic accuracy for distinguishing the TAFRO without iMCD/iMCD-TAFRO group from the other groups. Post-treatment, all patients with TAFRO without iMCD/iMCD-TAFRO showed improvement in CT readings, whereas only half of the patients with iMCD-NOS group showed changes. These findings emphasize the importance of CT-detected anterior mediastinal lesions in the diagnosis of TAFRO without iMCD/iMCD-TAFRO and warrant further research to validate these results.